PORTRAYAL OF RACIAL DISCRIMINATION IN MICHAEL JACKSON’S BLACK OR WHITE AND NEIL YOUNG’S SOUTHERN MAN - Muhammad Dzul Fadly (Indonesian Journal of Social Sciences and Humanities, 2020)
This study investigates the portrayal of racial discrimination in Michael Jackson’s Song Black or White and Neil Young’s Southern Man. Researcher identifies the racial issues in both songs, explaining the meaning that is implied in Michael Jackson’s Black or White and Neil Young’s Southern Man lyrics which relate to the words that possibly as indicators of racial discrimination. In this study researcher uses descriptive method in analyzing and interpreting the data collected. Data are collected from variety of sources such as books, journal, online website, and some additional information. The findings from the study show that both songs represent the disagreement and resistance of the fatal thoughts of treating people differently just because of the racial differences. Researcher concludes that in Michael Jackson’s Black Or White and Neil Young’s Southern Man the portrayal of racial discrimination clearly represented through the lyrics. The meanings of each song is lie on the historical background that influence the emergence of such songs.